2000
DOI: 10.1080/001401300404760
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of acoustic beacon characteristics for navigation tasks

Abstract: The goal of the present study was to investigate the human factors issues related to acoustic beacons used for auditory navigation. Specific issues addressed were: (1) the effect of various beacon characteristics on human accuracy in turning toward the direction of the acoustic beacon; (2) the difference between real and virtual environments on human accuracy in turning toward the acoustic beacon; and (3) the perceived sound quality of various acoustic beacons. Three experiments were conducted in which acousti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…Once the user reaches the waypoint indicated by the beacon, the sound shifts to represent the location of the next waypoint, the user reorients, and then the user sets off on the next path segment. As pointed out, Tran et al (2000) reported that specific sounds can lead to better localization and thus better performance in this sort of task.…”
Section: Beacons and Capture Radius In The Swanmentioning
confidence: 91%
See 2 more Smart Citations
“…Once the user reaches the waypoint indicated by the beacon, the sound shifts to represent the location of the next waypoint, the user reorients, and then the user sets off on the next path segment. As pointed out, Tran et al (2000) reported that specific sounds can lead to better localization and thus better performance in this sort of task.…”
Section: Beacons and Capture Radius In The Swanmentioning
confidence: 91%
“…Speech beacons are harder to localize in a virtual environment than are nonspeech beacons (Tran, Letowski, & Abouchacra, 2000). Users also give speech beacons low ratings for quality and acceptance (Tran et al, 2000). The speech-based interface cannot display a large amount of information, as two or more speech beacons presented simultaneously are difficult to attend to, given the limited human speech-processing capacity (e.g., Mowbray, 1953;Mowbray & Gebhard, 1961).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their study, simple waveforms, such as sine waves, produce the best acoustic beacon, whereas complex ones, such as speech, produce poorer beacons. These studies also indicate that auditory distances are harder to estimate accurately than are visual ones, in part due to acoustic parameters being more variable than light-based ones (Bronkhorst & Houtgast, 1999;King, Schnupp, & Doubell, 2001;Mershon et al, 1989;Tran et al, 2000). These studies support the impact of auditory information on the perception of space and suggest that acoustic information may well contribute to the perception of body tilt.…”
Section: Auditory Spatial Perceptionmentioning
confidence: 60%
“…These findings demonstrated that when room reflectance is low, perceived distance is underestimated and that when room reflectance is high, perceived distance is overestimated. Tran, Letowski, and Abouchacra (2000) demonstrated that localization error is influenced by the type of sound used as a beacon. According to their study, simple waveforms, such as sine waves, produce the best acoustic beacon, whereas complex ones, such as speech, produce poorer beacons.…”
Section: Auditory Spatial Perceptionmentioning
confidence: 99%